Application of Nonisothermal Cure Kinetics to the Interaction of Poly(ethylene terephthalate) with Alkyd Resin Varnish - Dias, D. S. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Kobelnik, M. [UNESP] (John Wiley & Sons Inc, 2011)
Samples of varnish (V), poly(ethylene terephthalate) from recycled soft drink bottles (PET-R), and varnish/poly(ethylene terephthalate) from recycled soft drink bottles mixtures (VPET-Rs) were evaluated with differential scanning calorimetry (DSC) to verify their physicochemical properties and thermal behavior. Films from V and VPET-R were visually similar. The maximum amount of PET-R that we could add to V without significantly altering its filming properties, such adherence and color in glass sheets, was 2%. The cure process (80-203 degrees C) was identified through the DSC curves. The kinetic parameters, activation energy (E), and Arrhenius parameter (A) for the samples containing 0.5-2% PET-R were calculated with the Flynn-Wall-Ozawa isoconversional method. With greater amounts of PET-R added, there was a small change in E for the curing process. A kinetic compensation effect, represented by the equation ln A = -10.5 + 0.29E, was observed for all of the samples. The most suitable kinetic model to describe this curing process was the autocatalytic Sestak-Berggren model, which is applied to heterogeneous systems governed by nucleation and growth. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 119: 1316-1321, 2011
Keywords: poly(ethylene terephthalate); resin; kinetics